2019
DOI: 10.1007/s11357-019-00079-x
|View full text |Cite
|
Sign up to set email alerts
|

ADNP differentially interact with genes/proteins in correlation with aging: a novel marker for muscle aging

Abstract: Activity-dependent neuroprotective protein (ADNP) is essential for embryonic development with ADNP mutations leading to syndromic autism, coupled with intellectual disabilities and motor developmental delays. Here, mining human muscle gene-expression databases, we have investigated the association of ADNP transcripts with muscle aging. We discovered increased ADNP and its paralogue ADNP2 expression in the vastus lateralis muscle of aged compared to young subjects, as well as altered expression of the ADNP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Akap6, Foxp2 , and Myl9 showed the most abundant correlations across tissues, age, and sex ( Figure 2 A). Interestingly Nmnat1 , which was correlated before with ADNP expression in human muscle [ 19 ], showed a highly significant correlation with Adnp in the GC muscle in the youngest group of males ( Figure 2 A). Comparing males to females suggested a more significant Adnp transcript correlation effect in males.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Akap6, Foxp2 , and Myl9 showed the most abundant correlations across tissues, age, and sex ( Figure 2 A). Interestingly Nmnat1 , which was correlated before with ADNP expression in human muscle [ 19 ], showed a highly significant correlation with Adnp in the GC muscle in the youngest group of males ( Figure 2 A). Comparing males to females suggested a more significant Adnp transcript correlation effect in males.…”
Section: Resultsmentioning
confidence: 93%
“…Further referring to the mechanism, our original studies identified a high degree of correlation between ADNP and NMNAT1 in the human muscle [ 19 ]. Here, a high correlation was discovered between Adnp and Nmnat1 expression in the young male mouse muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking at neuromuscular diseases, those may be more prevalent in males, with tauopathy/ADNP and microtubule disruption playing a role (Ivashko-Pachima, Seroogy, et al, 2021;Kapitansky & Gozes, 2019;Kapitansky, Karmon, et al, 2020;.…”
Section: More On Tau and Sexmentioning
confidence: 99%